A Review on Expression, Pathological Roles, and Inhibition of TMPRSS2, the Serine Protease Responsible for SARS-CoV-2 Spike Protein Activation. (26th July 2021) - Sarker, Jyotirmoy; Das, Pritha; Sarker, Sabarni; Roy, Apurba Kumar; Momen, A. Z. M. Ruhul
Abstract : SARS-CoV-2, the coronavirus responsible for the COVID-19 pandemic, uses the host cell membrane receptor angiotensin-converting enzyme 2 (ACE2) for anchoring its spike protein, and the subsequent membrane fusion process is facilitated by host membrane proteases. Recent studies have shown that transmembrane serine protease 2 (TMPRSS2), a protease known for similar role in previous coronavirus infections, severe acute respiratory syndrome (SARS), and Middle East respiratory syndrome (MERS), is responsible for the proteolytic cleavage of the SARS-CoV-2 spike protein, enabling host cell fusion of the virus. TMPRSS2 is known to be expressed in the epithelial cells of different sites including gastrointestinal, respiratory, and genitourinary system. The infection site of the SARS-CoV-2 correlates with the coexpression sites of ACE2 and TMPRSS2. Besides, age-, sex-, and comorbidity-associated variation in infection rate correlates with the expression rate of TMPRSS2 in those groups. These findings provide valid reasons for the assumption that inhibiting TMPRSS2 can have a beneficial effect in reducing the cellular entry of the virus, ultimately affecting the infection rate and case severity. Several drug development studies are going on to develop potential inhibitors of the protease, using both conventional and computational approaches. Complete understanding of the biological roles of TMPRSS2 is necessary before such therapies are applied.